(untitled) (Bioagro, 2020)
In Venezuela there are very few studies related to the search for crops that express resistance to nematodes attack. Six common bean genotypes (‘Anadelina’, ‘Bicentenaria’, ‘Carmelinia’, ‘Media Rama’, ‘Silvinera’, and ‘Tacarigua’) were evaluated for their reaction to the root-knot nematode M. javanica. All the genotypes allowed nematode infection and reproduction. The maximum rate of nematode reproduction was observed on the cultivars Carmelinia (12.49) and Tacarigua (12.28). Nematode infection suppressed (P≤0.05) total fresh weight, top fresh weight and top dry weight compared to the uninoculated controls of all common bean genotypes except those of ‘Tacarigua’, which showed tolerance to the nematode. The absence of resistant materials in the genotypes evaluated prevents their use as a source of resistance in breeding programs.